Financial Sustainability On Islamic Banking: Intellectual Capital And Knowledge Management - Purbayati, Radia; Hatma Juniwati, Endang; Pakpahan, Rosma; hadiani, fatmi; Aini, Nurfina (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
Intellectual Capital is one of the most important factors that can affect the company's performance from the capital aspect, including employee productivity, improving company skills, increasing company profits and creating a sustainable competitive advantage. In addition, Knowledge Management is also an important factor affecting bank performance. Effective knowledge management can improve operational efficiency, decision-making processes, and innovation capabilities within financial institutions, ultimately leading to improved sustainable financial performance. Therefore, this study aims to identify the effect of non-physical capital in the form of intellectual capital and knowledge management simultaneously on sustainable financial performance in Islamic banking. The urgency of the research is important to provide direction for increasing market share, optimizing intellectual capital, and knowledge management in achieving global sustainable competitive advantage of Indonesian Islamic banking. The research shows that the best model in testing is to use the Random Effect Model (REM). SCE, RCE and KM variables are variables that have a significant effect in the model with a positive direction. Meanwhile, HCE and CEE variables do not have a significant effect on the model.